Systematic Literatur Review : Pemanfaatan Augmented Reality Sebagai Alternatif Media Pembelajaran Matematika - Muhammad Fajar Anugrah; Dadan Dasari; Dadang Juandi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
Augmented Reality is currently one of the alternative technology-based learning media in the educational sphere. In this article, researchers conduct a review of existing research over the past 5 years, to determine the extent to which Augmented Reality is utilized in the mathematics learning process at schools using the Systematic Literature Review method. The process of submitting articles uses publish or perish tools with inclusion and exclusion article criteria related to the keywords that have been entered. Found 20 articles that meet these criteria. The result is a discussion of aspects of the utilization of augmented reality media, such as: the output of augmented reality forms, school grades using augmented reality, country locations using augmented reality, learning materials in school mathematics using augmented reality, to the benefits/purposes of its use.